The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3389/ti.2022.10073
|View full text |Cite
|
Sign up to set email alerts
|

Illness Perceptions and Medication Nonadherence to Immunosuppressants After Successful Kidney Transplantation: A Cross-Sectional Study

Abstract: Background: Medication nonadherence to immunosuppressants is a well-known risk factor for suboptimal health outcomes in kidney transplant recipients (KTRs). This study examined the relationship between illness perceptions and medication nonadherence in prevalent Dutch KTRs and whether this relationship depended on post-transplant time.Methods: Eligible KTRs transplanted in Leiden University Medical Center were invited for this cross-sectional study. The illness perceptions and medication nonadherence were meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 36 publications
(42 reference statements)
0
7
0
Order By: Relevance
“…Similarly, patients with hepatitis C who have a positive illness perception are more confident in their abilities to deal with diseaserelated challenges and have better physical and mental health outcomes (Langston et al, 2018). Conversely, other researchers believe that psychoeducational interventions can reduce the negative illness perception of kidney transplant recipients, hence enhancing medication adherence and quality of life (Látos et al, 2022;Wang et al, 2022). These findings imply that healthcare teams should assist kidney transplant recipients in identifying the causes of their negative illness perceptions and then utilize psychological intervention techniques to help them develop a more positive attitude about their condition; for example, they encourage patients to be optimistic about the future and to feel a sense of control over their lives following transplantation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, patients with hepatitis C who have a positive illness perception are more confident in their abilities to deal with diseaserelated challenges and have better physical and mental health outcomes (Langston et al, 2018). Conversely, other researchers believe that psychoeducational interventions can reduce the negative illness perception of kidney transplant recipients, hence enhancing medication adherence and quality of life (Látos et al, 2022;Wang et al, 2022). These findings imply that healthcare teams should assist kidney transplant recipients in identifying the causes of their negative illness perceptions and then utilize psychological intervention techniques to help them develop a more positive attitude about their condition; for example, they encourage patients to be optimistic about the future and to feel a sense of control over their lives following transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has revealed that kidney transplant recipients who perceive their condition more negatively report lower quality of life and more maladaptive coping strategies (Knowles et al, 2016;Kalfoss et al, 2019). Additionally, other researchers noted that medication non-compliance was reported by 32.4% of kidney transplant recipients, while having a positive outlook on one's health improved medication adherence and patient outcomes (Massey et al, 2013;Wang et al, 2022). According to Zelikovsky and Nelson (2021), an adolescent kidney transplant recipient's negative beliefs and perceptions about their illness negatively impact their well-being beyond the physical effects of their illness and medications.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, unhelpful illness perceptions are common and identified as important risk factors for health outcomes among patients in different CKD stages, including HRQOL, kidney function, or graft function ( 12 , 14 , 15 ). Moreover, past research has shown that unhelpful illness perceptions are modifiable by means of psycho-educational support strategies and can lead to improved coping behaviors and health outcomes ( 17 , 18 , 45 ). Future studies in KTRs are needed to: 1) further explore the role of illness perceptions in the relationship between symptom experience and HRQOL at a stable stage to provide further information for clinical practice, 2) explore the mediation effect of individual illness perceptions to provide more precise intervention targets, and 3) explore whether support strategies targeting unhelpful perceptions indeed lead to improved outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…If the score of the depression measurement indicated definite clinical depression, the researchers would contact the respondent to facilitate a referral to an outpatient psychological clinic for further assistance. The sample size for this cross-sectional study was calculated to be 966 using PASS 2021 software with a power of 0.95, an effect size of 6% and a proportion of 32.4% 3. Considering the dropout rate of 10%, 1063 participants were needed in this study.…”
Section: Methodsmentioning
confidence: 99%
“…Medication non-adherence refers to the situation in which patients fail to comply with prescribed medication therapy intentionally or unintentionally, consequently influencing the desired effect of drugs 2. Non-adherence to immunosuppressant medication is regarded as a significant risk factor for acute rejection, graft loss and allograft dysfunction following transplantation 2 3. Nonetheless, the prevalence of medication non-adherence in SOT recipients remains high worldwide.…”
Section: Introductionmentioning
confidence: 99%